A Troubled Beginning: Rome and its Reluctant Allies in the Fourth Century bc*. (26th October 2017) - Helm, Marian
Abstract: This article examines the origins of the Roman alliance system in the second half of the 4th century. The significance of the allies for the creation of a Mediterranean empire is undisputed; allied troops provided the Roman Republic with a manpower reservoir unmatched by any of its opponents. However, the stunning achievement of incorporating defeated foes into the military in equal numbers to Roman troops has been somewhat neglected and been taken as a given fact. A careful analysis of the years following the Latin War and the Samnite Wars reveals a constellation which does not suggest that the immediate creation of a more or less beneficial system of alliances was a primary Roman objective. Instead it will be argued that the evidence indicates a rather different development, where the challenge of organising and integrating the captured territory was a dynamic and at times arduous process, for which the setbacks – and indeed the crisis – of the so-called Second Samnite War served as a major catalyst.